Characterizing the trajectories of vasomotor symptoms across the menopausal transition. Issue 10 (October 2016) - Tepper, Ping G.; Brooks, Maria M.; Randolph, John F.; Crawford, Sybil L.; El Khoudary, Samar R.; Gold, Ellen B.; Lasley, Bill L.; Jones, Bobby; Joffe, Hadine; Hess, Rachel; Avis, Nancy E.; Harlow, Sioban; et al.
Abstract : Supplemental Digital Content is available in the text Abstract: Objective: The aim of the study was to investigate the heterogeneity of temporal patterns of vasomotor symptoms (VMS) over the menopausal transition and identify factors associated with these patterns in a diverse sample of women. Methods: The Study of Women's Health Across the Nation is a multisite longitudinal study of women from five racial/ethnic groups transitioning through the menopause. The analytic sample included 1, 455 women with nonsurgical menopause and a median follow-up of 15.4 years. Temporal patterns of VMS and associations with serum estradiol and follicle-stimulating hormone, race/ethnicity, body mass index, and demographic and psychosocial factors were examined using group-based trajectory modeling. Results: Four distinct trajectories of VMS were found: onset early (11 years before the final menstrual period) with decline after menopause (early onset, 18.4%), onset near the final menstrual period with later decline (late onset, 29.0%), onset early with persistently high frequency (high, 25.6%), and persistently low frequency (low, 27.0%). Relative to women with persistently low frequency of VMS, women with persistently high and early onset VMS had a more adverse psychosocial and health profile. Black women were overrepresented in the late onset and high VMS subgroups relative to white women. Obese women were underrepresented in the late onset subgroup. In multivariable models, the pattern of estradiol over the menopause was significantly associated with the VMS trajectory. Conclusions: These data distinctly demonstrate heterogeneous patterns of menopausal symptoms that are associated with race/ethnicity, reproductive hormones, premenopause body mass index, and psychosocial characteristics. Early targeted intervention may have a meaningful impact on long-term VMS.